PERTEMUAN IBU CERDAS SADAR GIZI DALAM “PROGRAM AKU SEHAT 2023” - Rizky Kurniati, S.ST., M.Kes., Fitria (LPPM ISTeK ICsada Bojonegoro, 2024)
Health maintenance is an effort to overcome and prevent health problems that require examination, treatment, care, including pregnancy and childbirth. Health education is the process of helping someone, by acting individually/collectively to make decisions based on knowledge about matters that affect their personal health and that of others. Pregnancy is a normal event and an important part of human life. The physical changes in pregnancy move gradually, but ultimately affect the woman's entire organ system. In general, the targets for this activity are residents of Gayam village, namely prospective brides and grooms, pregnant women and breastfeeding mothers. The number of participants in this activity consisted of 55 participants. The method used is to provide outreach and health education to the targets. The programs or activities provided are based on data and findings in the field, then evaluation of the activities will be carried out and follow up will be carried out on each activity The process of activities for the Meeting of Smart Nutrition Aware Mothers in the